The image of the Russian Enlightened Monarch in the Romanian culture at the end of the eighteenth and beginning of the nineteenth century - Chiriac, Alexandra; Catană-Spenchiu, Ana (Swedish Journal of Romanian Studies, 2022)
This paper aims to reconstruct the way in which the Romanian written culture from the second half of the eighteenth century and the beginning of the nineteenth gradually built the image of the Russian Enlightened monarchy with three of its most famous representatives: Peter II, Catherine II and Alexander I. By means of translating from Italian and German historiography, these texts served a double goal: on the one hand they satisfied the reader’s need for knowledge and understanding of the contemporary events, and on the other they contributed to a political discourse that viewed Russia and the Russian Orthodox monarchy as potential saviours of the Romanian principalities from the oppression of the Muslim Ottoman Empire. By means of translation analysis, we have attempted to illustrate how the Western image of an Eastern monarch, guided by a blend of Western philosophy and Eastern Orthodox tradition, was transferred in the Romanian culture as a scientific base for political and cultural decisions.